Metabolic response to fasting predicts weight gain during low-protein overfeeding in lean men: further evidence for spendthrift and thrifty metabolic phenotypes. Issue 3 (7th June 2019) - Hollstein, Tim; Ando, Takafumi; Basolo, Alessio; Krakoff, Jonathan; Votruba, Susanne B; Piaggi, Paolo
ABSTRACT: Background: Greater increase in 24-h energy expenditure (24EE) during overfeeding and smaller decrease in 24EE during fasting ("spendthrift" metabolic phenotype) are associated with more weight loss during sustained caloric restriction in overweight subjects. Objectives: The aim of this study was to investigate whether these acute metabolic responses can also predict weight gain during sustained overfeeding in lean individuals. Methods: Seven lean men participated in this study. Prior to overfeeding, 24EE responses to fasting and 200% normal-protein overfeeding were measured in a whole-room indirect calorimeter. Volunteers underwent 6 wk of 150% low-protein (2%) overfeeding followed by another wk of weight-maintaining diet, during which 24EE was revaluated. Body composition, 24EE, and various hormone concentrations, including fibroblast growth factor 21 (FGF21), were assessed at baseline, at wk 1, 3, and 6 of the overfeeding period, and 1 wk following overfeeding through the use of dual-energy X-ray absorptiometry, indirect calorimetry, and ELISA. Cumulative energy surplus was calculated from 24EE, daily physical activity, and direct measurements of calories of nutrient intake, feces, and urine by bomb calorimetry. Results: The average weight gain during 6 wk of low-protein overfeeding was 3.8 kg (6.1%, min: +2.5%, max: +8.0%). During 24-h fasting at baseline, 24EE decreased on average (mean ± SD) by 158 ± 81 kcal/d ( P = 0.007). Subjects with less 24EE decrease during fasting (more metabolically spendthrift individuals) gained less weight ( r = −0.84, P = 0.03), less fat mass ( r = −0.81, P = 0.049), and stored less calories ( r = −0.91, P = 0.03) during overfeeding. Following overfeeding, increased 24EE above requirements for achieved body size was associated with less weight and fat mass gain ( r = −0.78, P = 0.04) and with the increase in 24EE during 200% normal-protein overfeeding measured at baseline ( r = 0.91, P = 0.005). Serum FGF21 concentrations increased up to 44-fold during overfeeding ( P < 0.0001). Conclusions: Low-protein overfeeding may be an important tool to identify metabolic phenotypes (spendthrift compared with thrifty) that characterize susceptibility to weight gain. This trial was registered at clinicaltrials.gov as NCT00687115.